Exchange Rates, Inflation, and Nickel Export Value: A Comparative Panel Study - Tarizyah Amanda; Sri Astuty; Diah Retno Dwi Hastuti; Irwandi; Muhammad Imam Ma'ruf (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: The present study analyzes the impact of the exchange rate and inflation on nickel exports from three prominent producers in the Asia-Pacific region with disparate economic development levels. Design/methodology/approach: The present study utilizes annual panel data from 2000 to 2024, encompassing 75 observations, to examine the impact of the exchange rate (ER) and inflation (I) on the export of nickel (NEV) using a panel regression model. The specifications of the model were determined through the implementation of the Chow test and the Hausman test. Findings: The exchange rate exerts a positive and significant influence on the export of nickel, while inflation has not demonstrated a substantial impact. This model accounts for 40.5% of the variation in nickel exports, suggesting that factors external to the firm, such as global demand, commodity prices, and international market dynamics, play a significant role in determining export performance. Originality / value: The novelty of this research lies in the cross-country comparative panel approach that identifies variations in the macroeconomic response of nickel exports in three major nickel-producing countries in the Asia-Pacific region with different structural characteristics, expanding the empirical understanding of the sensitivity of strategic commodity trade to exchange rate fluctuations and inflation dynamics. Practical Implications: The results of the study indicate that exchange rates have become a primary factor in the performance of nickel exports, with domestic inflation having a negligible impact on the statistics. This study has expanded the understanding of the sensitivity of export commodities to strategic variables in macroeconomics and the mechanisms of transmission of mark swaps in mineral trade at different stages of development.